Antimicrobial activities of medicinal plants containing phenolic compounds - DİKPINAR, TUĞÇE (Bentham Science Publishers, 2020)
Background: Medicinal plants have been used to treat diseases for centuries. They are important sources in terms of their pharmacological effects and also have many microbial agents. Recently, the development of drug resistance has begun to spread in human pathogens against used antibiotics and this has led to new research for novel antimicrobial substances from natural products containing plants. Objective: The purpose of this review is to determine the antimicrobial activity of pure phenolic compounds isolated from medicinal plants, to evaluate how molecular structures of these compounds affect the activity, and to provide to the readers a source for future studies on natural antimicrobial agents. Methods: Relevant information was gathered from scientific engines and databases (Google Scholar, Web of Science, Scifinder, Science Direct, Scopus, Wiley Online Library, PubMed, Taylor & Fran-cis online) using different keywords. Antimicrobial activity research was selected especially on pure phenolic compounds. Results: Numerous phenolic compounds were isolated from plants/plant extracts and were shown to prevent the growth of bacteria and fungi and their Minimum Inhibition Concentration (MIC) and inhibition zone values were given in detail. Conclusion: This review revealed that phenolic compounds found in medicinal plants have different antimicrobial activity according to their changes in the molecular structure. © 2020 Bentham Science Publishers.
Keywords: Antibacterial activity; Antifungal activity; Medicinal plants; Microorganisms; Phenolic; Resistance